Identification of clinically useful predictive genetic variants in pachyonychia congenita. (1st July 2021) - Samuelov, L.; Sarig, O.; Adir, N.; Pavlovsky, M.; Smith, F. J.; Schwartz, J.; Hansen, C. D.; Sprecher, E.
Summary: Background: Pachyonychia congenita (PC) refers to a group of autosomal dominant disorders caused by mutations in five keratin genes ( KRT16, KRT6A, KRT17, KRT6B or KRT6C ). Current disease classification is based on the gene harbouring disease‐causing variants. Aims: We harnessed the International Pachyonychia Congenita Research Registry (IPCRR) containing both clinical and molecular data on patients with PC worldwide, to identify genetic variants predicting disease severity. Methods: We ascertained 815 individuals harbouring keratin mutations registered in the IPCRR. We looked for statistically significant associations between genetic variants and clinical manifestations in a subgroup of patients carrying mutations found in at least 10% of the cohort. Data were analysed using χ 2 and Kruskal–Wallis tests. Results: We identified five mutations occurring in at least 10% of the patients registered in the IPCRR. The KRT16 p.L132P mutation was significantly associated with younger age of onset, presence of palmar keratoderma oral leucokeratosis and a higher number of involved nails. By contrast, the KRT16 p.N125S and p.R127C mutations resulted in a milder phenotype featuring a decreased number of involved nails and older age of onset. Patients carrying the p.N125S mutation were less likely to develop palmar keratoderma while p.R127C was associated with an older age of palmoplantar keratoderma onset. Moreover, the KRT17 p.L99P mutation resulted in an increased number of involved fingernails and patients demonstrating 20‐nail dystrophy, while the opposite findings were observed with KRT17 p.N92S mutation. Conclusions: We have identified novel and clinically useful genetic predictive variants in the largest cohort of patients with PC described to date.